A comparative study of the reputation of Iraqi stock exchange companies before and after the presence of ISIS (Entrepreneurship Journal for Finance and Business, 2023)
The purpose of this research is to study the impact of the presence of ISIS in Iraq on the reputation of joint-stock companies in this country. For this purpose, the accepted reputation of companies in the Iraqi Stock Exchange was measured through a regression model and using the hypothetical variable regarding the presence of ISIS in Iraq, the topic was investigated.The method of conducting this research is descriptive-correlational, and the selected sample includes 35 companies that were listed on the Iraqi stock market during the years 2013 to 2018. The research hypotheses were tested using a multiple logistic regression model based on panel data.   The results of this research indicate that there is a significant relationship between the presence of ISIS in Iraq and the reputation of companies accepted on the stock exchange of this country, which means that the reputation of companies on the Iraqi stock exchange decreased with the presence of ISIS in Iraq.Keywords: company reputation, ISIS, Iraqi economy, logistic regression.